Efficacy on Biomass and Carbon Stock Production by Different Silvipasture Systems in Chambal Ravines of South-Eastern Rajasthan (India) - S, Kala; Parandiyal, A.K.; Mina, B.L.; Kumar, Ashok; Meena, H.R.; Reeja, S; Rashmi, I (Indian Journal of Agroforestry, 2022)
Selection of species with high carbon sequestration potential becomes more  important in the context of productive and effective utilization of degraded ravine lands. The protection of existing forests, reforestation of degraded forests and creation of new forestry and agroforestry plantations in India have been viable option for contributing to enhanced carbon stock production and atmospheric carbon balance management. The efficacy of carbon stock production depends choice of species, grow rate, age of tree, density of trees and other inherent wood forming traits. Maximum mean aboveground biomass (71.27 t ha−1), belowgroundbiomass (14.25 t ha−1), litter biomass (2.39 t ha−1)and total biomass (85.76 t ha−1) were recorded in the Acacia nilotica based silvipasture land use system. Total biomass production of different land use systems were categorized according the overall biomass and carbon stock productivity in the following order: Acacia nilotica > Aegle marmelos > Pongamia pinnata and Emblicaofficinalis respectively. Maximum soil organic carbon stock (18.92 t ha− 1) was recorded in Acacia nilotica based silvipasture land use systems, however lowest soil organic carbon value of 12.05 t ha-1 was observed in Pongammia pinnata compare to other systems. Soil organic  carbon was decreased with increase in soil depth irrespective of the land use system. Biomass and carbon stock estimation results indicated that total carbon storage value was higher in Acacia nilotica followed by Aegle marmelos > Pongamia pinnata and Emblica officinalis. Acacia nilotica based silvipasture system has ranked first in larger biomass (AGB & BGB) as well as C-stock. Comprehensively, Acacia nilotica and Aegle maremelos would be appropriate hardy tree species for securing high efficacy on enhanced carbon sequestration in fragile chambal ravine ecosystems of south-eastern Rajasthan in India.